Critical to care : the invisible women in health services - Armstrong, Pat, 1945- (University of Toronto Press, 2008)
Through a gendered analysis, Critical to Care establishes a basis for discussing research, policy, and other actions in relation to the work of thousands of marginalized women and men every day.